Promoting secondary students' understanding of scientific concepts through a guided-inquiry laboratory: Polymers and their properties - Wanchai Noiwong (2018)
This study employed a guided-inquiry laboratory exercise to attempt to make learning science more meaningful for secondary students. The learning unit, comprised mainly of a laboratory exercise on tensile properties of composite polymers based on natural rubber, was developed and implemented by 94 secondary students in their chemistry courses. Students' understanding of the scientific concept was measured by using a pretest and a posttest. Students' perceptions of the laboratory exercise were assessed by using a Likert-scale questionnaire and through classroom observation. The results revealed that there was a significant increase in the mean scores of the posttest over those of the pretest, with a 39 percent gain. The students also showed a positive attitude toward the designed learning unit, both in the laboratory activity and in the group work. The results clearly indicated that the designed laboratory exercise was effective in promoting students' learning outcomes. © Common Ground, Wanchai Noiwong, Pranee Phinyocheep.